THE ROLE OF CASE-STUDY METHOD IN TEACHING FOREIGN LANGUAGES AND THEIR METHODOLOGICAL ANALYSIS - Abdug’aniyeva Iroda Abbos qizi (Web of Journals Publishing, 2023)
The article discusses about case-study method and explains that it is a tool that allows you to apply theoretical knowledge to solve practical problems. It is mentioned that the method promotes the development of independent thinking in students, the ability to listen and take into account an alternative point of view, and to express their own with reason.
Keywords: innovative activity, case-study method, accuracy, logic, purity, richness, appropriateness, expressiveness, impressiveness, teaching.